Standardisasi Mutu Simplisia Daun Tapak Liman (Elephantopus scaber L.) Berdasarkan Parameter Spesifik dan Nonspesifik - Candra, Heldi; Oktaviani, Fifin; Kusumawati, Aldhehita Ari (-, 2026)
This study aimed to standardize simplicia of tapak liman leaves (Elephantopus scaber L.), identify its phytochemical constituents, and evaluate its antibacterial activity against Shigella dysenteriae. The research employed a laboratory experimental design. Simplisia was prepared through sorting, washing, drying, and milling processes, followed by maceration using 96% ethanol. Phytochemical screening was conducted qualitatively, while specific and non-specific parameters were evaluated according to herbal standardization guidelines. Antibacterial activity was tested using the disc diffusion method. The results showed that the simplicia met quality requirements, with water content of 8.5%, drying loss of 9.75%, ash content of 15.1%, water-soluble extract of 15.6%, and ethanol-soluble extract of 11.68%. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins, tannins, phenolics, coumarins, and reducing sugars. The extract exhibited moderate antibacterial activity with inhibition zones ranging from 9.3 to 11.3 mm. These findings support the potential of E. scaber leaves as a candidate for standardized herbal medicine.